The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/adfm.202004375
|View full text |Cite
|
Sign up to set email alerts
|

Selective Surface Reconstruction of a Defective Iridium‐Based Catalyst for High‐Efficiency Water Splitting

Abstract: Development of robust catalysts for electrochemical water splitting is a critical topic for the energy conversion field. Herein, a precise electrochemical reconstruction of IrTe 2 hollow nanoshuttles (HNSs) is performed for oxygen and hydrogen evolution reactions (OER and HER), the two half reactions of water splitting. It is determined that the reconstruction of IrTe 2 HNSs can be regulated by adjusting the potential during electrochemical dealloying, in which mild and high potentials lead to the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 41 publications
(17 reference statements)
0
65
0
Order By: Relevance
“…[ 18 ] From this viewpoint, an energy favorable surface reconstruction process during the initial stage can significantly accelerate the catalytic kinetics and contribute to generate stable active sites, and thus considerably enhancing the OER performance. [ 19 ] It has reported that a low activation energy barrier for initiating surface reconstruction is crucial for achieving rapid and stable OER, [ 20 ] and the level of difficulty of the initiation of the surface reconstruction can be read from the onset overpotential of the catalysts, in which a lower onset overpotential means a lower energy barrier for surface reconstruction. [ 21 ] A rapid low‐barrier surface reconstruction can achieve rapid creation and stabilization of active centers for following long‐time operation, can reduce the whole energy consumption during the electrocatalysis, and enhance the overall reaction stability, which are highly desired for industrial‐scale production.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] From this viewpoint, an energy favorable surface reconstruction process during the initial stage can significantly accelerate the catalytic kinetics and contribute to generate stable active sites, and thus considerably enhancing the OER performance. [ 19 ] It has reported that a low activation energy barrier for initiating surface reconstruction is crucial for achieving rapid and stable OER, [ 20 ] and the level of difficulty of the initiation of the surface reconstruction can be read from the onset overpotential of the catalysts, in which a lower onset overpotential means a lower energy barrier for surface reconstruction. [ 21 ] A rapid low‐barrier surface reconstruction can achieve rapid creation and stabilization of active centers for following long‐time operation, can reduce the whole energy consumption during the electrocatalysis, and enhance the overall reaction stability, which are highly desired for industrial‐scale production.…”
Section: Introductionmentioning
confidence: 99%
“…[4,9,13] Ir-based composites with different morphologies have been developed and investigated as potential OER catalysts. [14,15,16] However, Ir cannot be efficiently used at a large scale because of its high cost, scarcity, and poor durability. Designing an Ir-based catalyst with a low loading, high mass specific activity, and adequate stability can solve these drawbacks; however, the activity of such catalyst would be hindered by the presence of unstable active Water electrolysis, which is a promising high-purity H 2 production method, lacks pH-universality; moreover, highly efficient electrocatalysts that accelerate the sluggish anodic oxygen evolution reaction (OER) are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when paired with commercial 20 wt% Pt/C, P-IrO x @ DG can deliver current densities of 350.0, 317.6, and 47.1 mA cm −2 sites and unfavorable reconstruction during operation. [16][17][18] Embedding Ir by conductive carbon substrates like graphene and carbon nanotubes may improve the catalytic stability and intrinsic activity. [19] High-temperature pyrolysis and hydrothermal/solvothermal processes are commonly used to prepare metal composite/carbon hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Ru/Ir‐based precious metal materials are deemed as the most excellent OER electrocatalysts, but their large‐scale applications are limited by their high cost and scarcity [5] . Therefore, it is necessary to develop high‐performance and earth‐abundant non‐noble metal catalysts for OER for industrial applications [4a,6] …”
Section: Introductionmentioning
confidence: 99%